2001
DOI: 10.1152/ajpgi.2001.281.1.g138
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of intestinal gas retention in humans: impaired propulsion versus obstructed evacuation

Abstract: To explore the clinical role of intestinal gas dynamics, we investigated two potential mechanisms of gas retention, defective propulsion and obstructed evacuation. In healthy subjects, a gas mixture was continuously infused into the jejunum (4 ml/min) 1) during a 2-h control period of spontaneous gas evacuation and 2) during a 2-h test period either with impaired gut propulsion caused by intravenous glucagon (n = 6) or with obstructed (self-restrained) anal evacuation (n = 10) while anal gas evacuation, sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 22 publications
2
71
0
Order By: Relevance
“…After including all published trials in which probiotics were tested to asses bloating or distension relief as primary or secondary endpoints in IBS or non IBS patients, conclusion was that specific probiotics can lead to bloating relief in some patients with IBS [117] . Experimental data in healthy controls showed that glucagon, a potent muscle relaxant, reduced abdominal symptoms but gas retention and objective abdominal distension were unaffected [77] . Domperidone has been shown to be ineffective in IBS symptoms [118] whereas the administration of neostigmine, a prokinetic drug, produced gas clearance and improvement of both abdominal symptoms and objective distension [119] .…”
Section: Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…After including all published trials in which probiotics were tested to asses bloating or distension relief as primary or secondary endpoints in IBS or non IBS patients, conclusion was that specific probiotics can lead to bloating relief in some patients with IBS [117] . Experimental data in healthy controls showed that glucagon, a potent muscle relaxant, reduced abdominal symptoms but gas retention and objective abdominal distension were unaffected [77] . Domperidone has been shown to be ineffective in IBS symptoms [118] whereas the administration of neostigmine, a prokinetic drug, produced gas clearance and improvement of both abdominal symptoms and objective distension [119] .…”
Section: Treatmentmentioning
confidence: 99%
“…They have suggested that while gas volumes may be normal in patients with bloating, they have an impaired intestinal handling of gas loads [57,67,76,77] . This may be of particular relevance since a sensory-motor gut abnormality might represent the pathophysiological basis of bloating.…”
Section: Impaired Abdominal Emptingmentioning
confidence: 99%
See 3 more Smart Citations